Protective low expression of PU.1 reduces microglial inflammatory and phagocytic response: Molecular and cell biology: Neurodegeneration versus neuroprotection. (7th December 2020) - Pimenova, Anna A.; Herbinet, Manon; Gupta, Ishaan; Machlovi, Saima; Marcora, Edoardo; Goate, Alison M.
Abstract: Background: The genetic risk for sporadic Alzheimer's disease (AD) is polygenic, driven by more than 40 loci. Pathway analysis implicates immune response in the etiology of AD, and given that genetic risk alleles are enriched in myeloid cell types, it has been proposed that impaired microglial function is a major contributing factor to AD risk. Microglial homeostasis is affected by the myeloid lineage‐determining transcription factor SPI1 /PU.1, with lower SPI1 expression associated with protection and higher expression with risk for AD based on the rs1057233 genotype. Methods: To understand how modulation of PU.1 expression affects microglial function we generated stable Spi1 /PU.1 overexpression and knock‐down BV2 mouse microglial cell lines and assessed their response in functional assays under baseline and challenged conditions using staurosporine, rotenone and LPS. Result: Analysis of RNA sequencing data from BV2 lines showed that knock‐down of PU.1 repressed the microglial homeostatic gene signature in a manner similar to that described in disease‐associated microglia in AD mouse models. Pathways of LXR/RXR signaling, antioxidant action and protein translation were upregulated, while inflammatory gene expression was decreased, which may underlie the protective effect of microglia with reduced PU.1 expression. BV2 microglial cells with PU.1 overexpression showed increased, while PU.1 knock‐down led to decreased phagocytosis of bioparticles independent of their type, e.g. zymosan, myelin, early or late apoptotic cells. PU.1 overexpression led to resistance to staurosporine‐induced apoptosis because of decreased caspase cascade activity, while PU.1 knock‐down cells were more susceptible to apoptosis‐induced cell death independent of caspase activation. Increased viability of PU.1 overexpressing cells resulted in potentiation of production of reactive oxygen species, nitric oxide and inflammatory cytokines under stimulated conditions. Furthermore, conditioned media from these cells led to propagation of the reactive phenotype to mouse primary astrocytes in culture. In contrast, PU.1 knock‐down repressed the inflammatory response of BV2 cells after LPS stimulation, and repressed the reactive phenotype in astrocytes. Conclusion: Reduced expression of PU.1 represses the homeostatic signature of microglia and decreases stimulus‐mediated cell viability, phagocytic and inflammatory responses, which may lead to increased turnover of microglia in the brain underlying the protective effect of SPI1 genotype against AD risk.